PELAKSANAAN NILAI DEMOKRASI DI KALANGAN MAHASISWA (Studi Kasus Pada Mahasiswa Program Studi PKN FKIP UMS Tahun Akademik 2014/ 2014) - Sri Gunarsi; Bayu Andri Nugraha; Tri Wahono (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2014)
The aim of the research is to describe the conducting of democracy values on students’ community in study program of Pancasila and kewarganegaraan education of FKIP-UMS in 2013/2014 Academic Year. The kind of research is qualitative with single case study strategy. Technique of data collection is by using interview, observation, and documentation. Data validity is by using technique and source of triangulation. Data analysis is by using interactive analysis. The research result showed that the conducting of democracy values on students’ community in study program of Pancasila and kewarganegaraan education of FKIP-UMS can be seen from the teaching learning process activity. The forms of conducting democracy values on students’ community in study program of Pancasila and kewarganegaraan education of FKIP-UMS were showed by: 1)Doing discussion with other students on teaching learning process in the classroom; 2) Giving input or opinion to other students on classroom discussion; 3) Receiving advice or critique from other students on classroom discussion; 4) Taking decision with cooperation towards things that have linked with academic activity outside the classroom; 5) Doing discussion with other students in doing group duty outside the classroom.